Pediatric Hodgkin’s lymphoma presenting with nephrotic syndrome: a case report - Hemal, Alok; Kumar, Bharat; Bhatnagar, Simran; Kumar, Nitish (International Journal of Contemporary Pediatrics, 2023)
Hodgkin’s lymphoma (HL) is a common type of lymphoma in children and adolescents, and it typically presents with lymphadenopathy, fever, and weight loss. Nephrotic syndrome is a rare but reported complication of HL, and it is associated with a poor prognosis. We report a case of a 12-year-old boy who presented with nephrotic syndrome as the initial manifestation of HL. The diagnosis was confirmed by a biopsy of the lymph node, which showed the characteristic Reed-Sternberg cells. The patient was treated with chemotherapy and he achieved complete remission of both HL and nephrotic syndrome. This report aims to raise awareness of the potential association between HL and nephrotic syndrome in pediatric patients, which can aid in early detection and prompt management.